Spolna razlika/spolna enakopravnost v jeziku/kulturi - Zupanc Ećimović, Paula (Annales. Series historia et sociologia, 2009)
In the article I present a contemporary reflection on the propositions concerning the problems of expressing and representing gender differentiation and gender equality in language/culture and the related practice in spoken language. I find categoriyations of genders in the scope of their mutual relations and in their relationship towards the cultural principals and systems particularly problematic, as they establish the practice of hierarchy of relations between the sexes, which is contrary to the practice of equality,supposedly intended with particular sexual subjects, through their imperatives established upon arbitrary social conventions. The arbitrary relationship towards the categorisation of grammatical gender has been consolidated through the entire development period of monotheistic dogmas during which the patriarchal social system marked by the undisputed rule of the male (gender) has been reinforced. According to arbitrary ideological decisions and principals the male gender had become the universal gender, the unmarked gender, representing a woman (female gender) as well. I emphasiye the questionability of the term neutrality associated with the phenomenon of genders, which - even through the representational form of language - must by no means become non-living categories of neither one or the other . I also stress the term equality, which is being used without reflection, as it contradicts contemporary constitutional principals of equality before the law for each individual on account of the fact that we are all different with respect to our sex, religious beliefs, sexual orientation, ethnicity, age, state of health, etc. I present the contemporary term sexual differences as a basic presumption of differentiation in the sense of a universal phenomenon. The question of representation of different gender subjects arises from the basic presumption of the necessity and the need for expressing difference (différence) as the only means of representing meanings. It is not only a question of difference, but also the question of the Other, the question of polisemic versus Equality/Unity. The balance between the sexes - symmetry ? does not exist, instead there is hierarchy - asymmetry. Upon the realiyation of the consequences of the existing linguistic situation, political and constitutional action has been undertaken within some languages and cultures, for instance the U.K. and U.S English, which has established the equality of expressing female and male gender
Keywords: govor; jezik; Language; slovnični spol; sociolinguistics; sociolingvistika; spolna enakost; spolna identiteta